Built-in reliability design of highly integrated solid-state power switches with metal bump interconnects - Li, Jianfeng; Castellazzi, Alberto; Dai, Tianxiang; Corfield, Martin; Solomon, Adane Kassa; Johnson, Christopher Mark (IEEE, 2015)
A stacked substrate-chip-bump-chip-substrate assembly has been demonstrated in the construction of power switch modules with high power density and good electrical performance. In the present work, special effort has been devoted to material selection and geometric shape of the bumps in the design for improving the thermo-mechanical reliability of a highly integrated bi-directional switch. Results from Three-dimensional finite element simulation indicate that for all design cases the maximum von Mises stresses and creep strain accumulations occur in the solder joints used to join bumps on IGBTs during a realistic mission profile, but occur in the solder joints used to join bumps on DBC substrates during accelerated thermal cycling. The results from both the simulation and the accelerated thermal cycling experiments reveal that selection of Cu/Mo/Cu composite brick bumps in the stacked assembly can significantly improve the thermo-mechanical reliability of both the solder joints and the DBC substrates when compared to Cu cylinder bumps and Cu hollow cylinder bumps reported in previous work. Such results can be attributed to the effective reduction in the extent of mismatch of coefficients of thermal expansion between the different components in the assembly.